Equity pledge of controlling shareholders and investment structure - Duan, Qianqi; Nor, Normaziah Mohd; Selamat, Aslam Izah (Asian Journal of Economic Modelling, 2024)
This study aims to explore the influence of the controlling shareholders' equity pledge on the company's investment structure and simultaneously investigate the regulatory effect of the ownership nature on the controlling shareholders' equity pledge and investment structure. We take China Shanghai and Shenzhen A-share listed companies as the research object, covering the data from 2013 to 2021, including 14,870 firm-year observations. The results show that the stock pledge behavior of the controlling shareholder tends to encourage the company to make more financial investments than physical investments. In addition, we find that ownership nature helps alleviate the above relationship to a certain extent. It is worth noting that non-manufacturing companies and non-big4 companies have a stronger positive impact on the company's investment structure than manufacturing companies and big4 companies. Finally, we also test the robustness of the research results using the propensity score matching method and the adding control variables method, which is consistent with the results of the baseline regression analysis. The proportion of equity pledged by controlling shareholders should be controlled, especially when the proportion of financial assets in the company's investment structure is too high. This measure can reduce the risk of financialization and maintain the stability of the financial market.